THE OPTIMIZATION OF TIME AND COST PROCESS TECHNIQUE (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
The critical path method (CPM) and linear programming are two closely related operations research techniques. Some of their concepts are presented in this paper in order to review some recent modelling structures that have been particularly valuable in the analysis of project time-cost crashes problems.The activities underwent crashing of both the time and cost using linear programming. A simplified representation of a small project and a linear programming model were formulated to represent this system. In addition to being simple, the advantage of this method is that it is applicable to large networks. It allows for a shorter computational time at a lower cost, whereas robustness is increased.Keywords: Critical path method, linear programming, time crashing, maintenance